2023
DOI: 10.3389/fmolb.2023.1223863
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics characterization of the microbial populations and chemical space composition of a water kefir fermentation

Maria Clara Arrieta-Echeverri,
Geysson Javier Fernandez,
Adriana Duarte-Riveros
et al.

Abstract: In recent years, the popularity of fermented foods has strongly increased based on their proven health benefits and the adoption of new trends among consumers. One of these health-promoting products is water kefir, which is a fermented sugary beverage based on kefir grains (symbiotic colonies of yeast, lactic acid and acetic acid bacteria). According to previous knowledge and the uniqueness of each water kefir fermentation, the following project aimed to explore the microbial and chemical composition of a wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…We found that LAB including Schleiferilactobacillus harbinensis, Lentilactobacillus kefiri, and Furfurilactobacillus rossiae (Table S2) were enriched (FDR P < 0.001 for all) in AAB dominant samples (samples with >25% AAB). S. harbinensis and L. kefiri are common members of water kefir, an acidic beverage which is often populated by AAB, suggesting shared acid tolerance (36,37). However, the most dominant LAB in sourdough (Levilactobacillus brevis, Lactiplantibacillus plantarum, Pediococcus parvulus, Fructilactobacillus sanfranciscensis) are found similarly with and without AAB.…”
Section: Resultsmentioning
confidence: 99%
“…We found that LAB including Schleiferilactobacillus harbinensis, Lentilactobacillus kefiri, and Furfurilactobacillus rossiae (Table S2) were enriched (FDR P < 0.001 for all) in AAB dominant samples (samples with >25% AAB). S. harbinensis and L. kefiri are common members of water kefir, an acidic beverage which is often populated by AAB, suggesting shared acid tolerance (36,37). However, the most dominant LAB in sourdough (Levilactobacillus brevis, Lactiplantibacillus plantarum, Pediococcus parvulus, Fructilactobacillus sanfranciscensis) are found similarly with and without AAB.…”
Section: Resultsmentioning
confidence: 99%